A national label for small-scale fisheries products-one way to improve competitiveness. (Research'eu results magazine)
How best to defend the rights of small-scale fishermen, ensure they receive fair pay and boost their competitiveness? The EU-funded SUCCESS project thinks one key step is to raise awareness and they are proposing to do so by labelling.